Effect of Ethanol Concentrations, Honey Adding and Maceration Times on Quality of Mao (Antidesma thwaitesianum) Liqueur - Dechkunchorn, Mayoonkarn; Phet-Tool, Sirilak; Suepchat, Panadda; Tinchan, Patcharaporn; Jumnongpon, Rattakorn (Trends in Sciences, 2024)
The Mao tree (Antidesma thwaitesianum) is a native and medicinal fruit tree found in Southeast Asia, thriving especially in dipterocarp forests, notably in Northeast Thailand’s Phu Phan valley. Ripe Mao fruits are rich in various nutrients and antioxidants that have the potential to mitigate the risk of chronic diseases and cancer. A comprehensive study was conducted to assess the impact of ethanol at different concentrations (40 or 60 % v/v), with and without honey added. The effects of varying maceration times (0, 3, 6, 9, or 12 months) on Mao liqueur’s properties were also investigated. The investigation explored various parameters, including color, total soluble solids, total acid content, alcohol concentration, and bioactive compounds. The results showed that the color lightness (L*) values of all recipes decreased over the storage period. However, adding honey to the production of Mao liqueurs decreased the yellowness (b*) value in the first 3 months but resulted in a higher total soluble solid content in Mao liqueur. Increasing the ethanol concentration from 40 to 60 % did not affect the total acid content (TTA 0.04 %). However, the addition of honey increased the total acid content from 0.04 to 0.08 % (p ≤ 0.05). The maceration time did not affect the alcohol content of Mao liqueur (p > 0.05). The use of 60 % (v/v) ethanol with honey addition resulted in the highest alcohol content (42 % v/v). Increasing the ethanol solution concentration from 40 to 60 % with and without honey added increased the total phenolic content from 126 to 165 GAE mg/L and 136 to 160 GAE mg/L respectively. The addition of honey increased the anthocyanin content in the liqueurs in the 12th month. HIGHLIGHTS Alcohol contents, maceration times and effect of honey adding were studied to improve the quality of liqueur made of Mao (Antidesma thwaitesianum) Mao liqueurs of 60 % EtOH had large changes in their alcohol contents during the maceration time 3 - 6 months Increasing the ethanol solution concentration from 40 to 60 % increased the total phenolic content The addition of honey increased the anthocyanin content in the liqueurs in the 12th month GRAPHICAL ABSTRACT